The relationship between selenium and viral diseases - Jiali Li; Jia Lai; Yuhui Zeng; Bing Zhu; Yinghua Li (Interdisciplinary Medicine)
Abstract Selenium (Se) is a trace element that fulfills vital functions in the organism. Over the past few years, numerous studies have revealed the profound connection between Selenium and its therapeutic potential in addressing various viral infectious diseases. Selenium can boost the activity of immune cells and counteract oxidative damage caused by free radicals to prevent the replication of viruses. Studies have shown that Selenium protects against a wide range of viruses such as DNA viruses, hepatitis B virus, RNA viruses, human immunodeficiency virus and coxsackie virus. Selenium is probably one of the research directions for antiviral drugs in the future. This review summarizes the use of Selenium in antiviral therapy and its research progress.